Two cases of embolic pneumonia associated with udder cleft dermatitis in dairy cattle from the same farm. Issue 3 (11th September 2017) - Turner, Andrea; Wood, Sarah; Millar, Michael
Abstract : Two Holstein cows from the same farm were presented within eight months of each other with malaise, milk drop and dyspnoea. Both cows had active or historic udder cleft dermatitis (UCD) lesions. Clinical examination and diagnostic tests led to an initial diagnosis of chronic suppurative pneumonia in both cows. The cases were poorly responsive to antibiotic treatment and died or were euthanased, 18 and 16 days respectively, after presentation. Postmortem examination of each case resulted in the diagnosis of embolic pneumonia associated with UCD. In both cases, UCD lesions, which were considered insignificant by the farmer and the veterinarian, are thought to have been the initiating source of infection. It is important that both farmers and vets are made aware of the possible severe consequences of udder cleft lesions and that early detection strategies for UCD and udder cleft lesions are adopted and implemented on‐farm.